A hybrid OTFT-SPR system for simultaneous electronic and optical sensing - Hatami, Davood; Hasler, Roger; Spanu, Andrea; Dostalek, Jakub; Kleber, Christoph; Knoll, Wolfgang; Bonfiglio, Annalisa (Scientific reports, 2025)
In this study, we present the development of an advanced multivariable sensing platform that combines a flexible extended-gate organic thin-film transistor (ExG-OTFT) with a surface plasmon resonance (SPR) readout of its sensing surface. This device architecture overcomes the limitations of prior combined SPR and field-effect transistor (FET)-based systems, thanks to the spatial separation of the sensing surface from the transistor body, and the implementation of a pseudo-reference electrode, which significantly improves the system reliability. We demonstrate the potential of this solution through the simultaneous electrical and optical detection of layer-by-layer formation of polyelectrolyte multilayers in real-time. While the SPR-based transduction is sensitive to local refractive index changes associated with a mass uptake on the sensing surface, the electronic transduction provides complementary information about collective charge carrier distribution. The ExG-OTFT architecture ensures compatibility with commercially available SPR instrumentation, enabling straightforward upgrades to SPR/FET functionality with minimal modifications. More interestingly, we introduce a flexible SPR/FET sensor, offering a scalable, robust and cost-effective solution (thanks to the use of convenient printing techniques for the fabrication of the organic FET) for multivariable sensing applications across diverse fields to advance the next generation of sensing platforms.
Keywords: Simultaneous electronic and optical detection; Extended Gate-OFET; Organic electronic sensors and biosensors; SPR